Massillon Rev. Ordinances, at 50-51, ch. 10, §§ 129-130 (1880). - (:unkn) unknown (My University, 1880)
That whoever carries any pistol, bowie knife, dirk, or other dangerous weapon, concealed on or about his person, shall be fined not more than two hundred dollars, or imprisoned not more than thirty days, and for a second offense, fined not more than five hundred dollars, or imprisoned not more than three months, or both.
Keywords: CARRY - CONCEALED